Transcendent meaning axiological orientations of individual - Держко, І.З. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The paper addresses the problem of axiological meanings metaphysical knowledge. We analyze hierarchical relationships between the value modalities, which gives an opportunity to show their importance to humans.